On Herzegovinian Sanjakbeys up Until the Establishment of the Bosnia Eyalet (Prilozi za orijentalnu filologiju, 2021)
The Ottomans attached great importance to Rumelia, i.e. the European part of their Empire. The economic and human resources of the area were enormous, so Rumelia represented a priority and a fundamental preoccupation in the military and foreign policy of the Ottoman sultans.The Ottoman political leadership carefully selected and appointed the leading people in its European provinces. This practice was particularly applied in so-called border strip sanjaks that were on the frontiers of the Empire and this is why the governing of these provinces was entrusted to prominent persons from among the frontier lords. Since the sanjak of Herzegovina was the frontier province since its foundation in 1470, the highest office was entrusted to dignitaries recommended by their ability or kinship with influential people in the sultan’s court. In the past period, this issue was touched upon by Ćiro Truhelka and Toma Popović, but their research was limited to documents from the Dubrovnik State Archives, mostly written in Italian. In this paper, we examine new information on this topic found in different Ottoman archival sources from Dubrovnik, Venice, Istanbul and Ankara, which helped us shed more light on the matter and correct some misconceptions.